2022
DOI: 10.1108/tr-12-2021-0539
|View full text |Cite
|
Sign up to set email alerts
|

Online customer reviews: insights from the coffee shops industry and the moderating effect of business types

Abstract: Purpose This study aims to explore the hidden connectivity among words by semantic network analysis, further identify salient factors accounting for customer satisfaction of coffee shops through analysis of online reviews and, finally, examine the moderating effect of business types of coffee shops on customer satisfaction. Design/methodology/approach Two typical major procedures of big data analytics in the hospitality industry were adopted in this research: one is data collection and the other is data anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Research has previously considered a six-month time period from several cities in the USA (Li et al , 2020; Luo and Xu, 2021; Tian et al , 2021; Xu, 2021) and the UK (Mathayomchan and Taecharungroj, 2020; Rahimi et al , 2022). Some studies narrow their research down to only fine-dining restaurants (Cassar et al , 2020; Harba et al , 2021; Saydam et al , 2022; Tao and Kim, 2022), green restaurants (Park et al , 2021) or single chain restaurants (DiPietro and Levitt, 2019); a sample may be formed randomly from collected reviews (Oh and Kim, 2021) or filtering and only studying positive ones in depth (Ahmad and Guzmán, 2021). Research has also covered the limited time period of the COVID-19 outbreak (Chen et al , 2020).…”
Section: Methodology and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Research has previously considered a six-month time period from several cities in the USA (Li et al , 2020; Luo and Xu, 2021; Tian et al , 2021; Xu, 2021) and the UK (Mathayomchan and Taecharungroj, 2020; Rahimi et al , 2022). Some studies narrow their research down to only fine-dining restaurants (Cassar et al , 2020; Harba et al , 2021; Saydam et al , 2022; Tao and Kim, 2022), green restaurants (Park et al , 2021) or single chain restaurants (DiPietro and Levitt, 2019); a sample may be formed randomly from collected reviews (Oh and Kim, 2021) or filtering and only studying positive ones in depth (Ahmad and Guzmán, 2021). Research has also covered the limited time period of the COVID-19 outbreak (Chen et al , 2020).…”
Section: Methodology and Datamentioning
confidence: 99%
“…We do not consider any methods based on survey analysis, like structural modeling, where eWOM may not be representative (Jeong and Jang, 2011). Some research study review sentiment (Hajek and Sahut, 2022; Kim et al , 2022; Mathayomchan and Taecharungroj, 2020; Tian et al , 2021), but this method could be misleading and uninformative, because of relying only on the sentiment of each word and not on the context of their usage (Rahimi et al , 2022; Tao and Kim, 2022; Vidal et al , 2015). The authors see case study and content analysis as an alternative for in-depth text analysis (Ng et al , 2021) or emotion labeling surveys (Oh and Kim, 2021), but they are both limited because they cannot cover the amount of existent data.…”
Section: Methodsmentioning
confidence: 99%
“…The volume of online reviews is widely used as a proxy to measure response, such as those of consumers and managers (Li et al , 2019; Chen et al , 2019; Xie et al , 2016; Kim et al , 2015). In the hospitality industry, the volume of online reviews positively affects the restaurant performance (Kim et al , 2016; Tao and Kim, 2022), hotel booking transaction values (Torres et al , 2015) and hotel occupancy rates (Viglia et al , 2016). Additionally, a positive effect of the volume of online reviews on RevPAR growth is found in unbranded or independent hotel chains (Raguseo and Vitari, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This theory helps to analyze how people are influenced by the opinion of friends, parents or close associates and how the people are influenced by the information relating to consumption of a product or service through internet (Kaur and Medury, 2011;Chatterjee, 2019b). Thus, in terms of socialization theory, internet usage and peer influence help the customers to be easily influenced by the online feedback (Hunter-Jones, 2014;Jayawardena et al, 2021;Tao and Kim, 2022). The Expectation Value Theory (EVT) (Fishbein and Ajzen, 1975) provides an effective theoretical framework to analyze the tendency of the customers to be involved in WOM through online platform (eWOM).…”
Section: Literature Review and Theoretical Underpinningmentioning
confidence: 99%